2020
DOI: 10.3171/2018.9.jns181768
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent posterior fossa anatomical differences in trigeminal neuralgia patients with and without neurovascular compression: a volumetric MRI age- and sex-matched case-control study

Abstract: OBJECTIVEThe pathophysiology of trigeminal neuralgia (TN) in patients without neurovascular compression (NVC) is not completely understood. The objective of this retrospective study was to evaluate the hypothesis that TN patients without NVC differ from TN patient with NVC with respect to brain anatomy and demographic characteristics.METHODSSix anatomical brain measurements from high-resolution brain MR images were tabulated; anterior-posterior (AP) prepontine cistern length, cerebellopontine angle (CPA) ciste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
2
14
1
1
Order By: Relevance
“…Subsequently, we performed a sex-dependent analysis ( Table 3 ). As a result, we revealed that the volume of PCF and its substructure in female was smaller than that in male (X, Z, and volume: p < 0.001; Y: p = 0.002), which was in line with the previous publications ( 18 ). Moreover, a more flat-shaped PCF was identified in both female and male cases with venous NVC compared with arterial NVC.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Subsequently, we performed a sex-dependent analysis ( Table 3 ). As a result, we revealed that the volume of PCF and its substructure in female was smaller than that in male (X, Z, and volume: p < 0.001; Y: p = 0.002), which was in line with the previous publications ( 18 ). Moreover, a more flat-shaped PCF was identified in both female and male cases with venous NVC compared with arterial NVC.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies indicated that the PCF morphometry might be similar in healthy subjects and classic TN patients (18,28,29). In addition, a smaller PCF was merely characterized as TNs without NVC, so-called idiopathic TNs (18). However, there were differences regarding the study design between previous works and our present work.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…We used the previously described methods to measure posterior fossa structures. 9,[19][20][21][22][23][24][25] Details in e-methods (links.lww. com/NXG/A252).…”
Section: Measurementsmentioning
confidence: 99%
“…75 We have now demonstrated that the size of the posterior fossa seems to have a striking impact on the development of TN1 in males and females. 40 We have also recently reported that knowledge of only two parameters prior to surgery, i.e., the diagnosis of TN1 and the grade of NVC (I-III), can accurately predict the pain-free outcome and durability of microvascular decompression postoperatively. 39 In general, most pains that are the consequence of nervous system injury (peripheral or central) are not improved by further injury to the nervous system, and may, in fact, worsen.…”
Section: Trigeminal Neuralgiamentioning
confidence: 96%